Non-monetary incentives in participatory sensing framework: a case of mobile health / Syarulnaziah Anawar - Anawar, Syarulnaziah (2018)
Non-communicable diseases (NCD), which are related to unhealthy lifestyles, cause a high proportion of deaths across the globe. This calls for a participatory sensing solution that may significantly expand access to healthcare to more people. Participatory sensing allows citizens to monitor activities, while enabling researchers and stakeholders to collect, analyse, and share local knowledge. However, in the absence of adequate participation, the participatory sensing system will fail to collect meaningful findings for decision making. Recent developments in the field of incentives have led to a renewed interest in non-monetary strategies to improve participants’ performance. Nevertheless, most of the studies typically addressed the extrinsic incentives and largely overlooked the intrinsic aspect of the non-monetary incentives, thus losing the potency to fulfil the needs of the data contributor holistically.